2015
DOI: 10.1017/s1368980015002384
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and covariates of food insecurity among residents of single-room occupancy housing in Chicago, IL, USA

Abstract: Objective: Emerging evidence suggests that food insecurity is a significant public health concern among people who are homeless or marginally housed. The present study assessed prevalence of food insecurity and its covariates among a group of marginally housed individuals living in single-room occupancy (SRO) dwellings, a population for which there is little extant health or nutrition research. Design: Cross-sectional survey incorporating the Household Food Insecurity Access Scale. Setting: Ten private SRO res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 52 publications
1
16
0
1
Order By: Relevance
“…In a population-based sample of older homeless adults, over half reported food insecurity: one-third reported low food security and one quarter reported very low food security. This is similar to food insecurity estimates among other homeless populations [27][28][29][30] and two times higher than national estimates in the US poverty population (below 185% of the poverty threshold). 31 In the general population, older adults are less likely to experience food insecurity than younger adults.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In a population-based sample of older homeless adults, over half reported food insecurity: one-third reported low food security and one quarter reported very low food security. This is similar to food insecurity estimates among other homeless populations [27][28][29][30] and two times higher than national estimates in the US poverty population (below 185% of the poverty threshold). 31 In the general population, older adults are less likely to experience food insecurity than younger adults.…”
Section: Discussionsupporting
confidence: 81%
“…Prior studies in homeless non-elderly populations found similar prevalence of food insecurity, with estimates between 40 and 64%. [27][28][29][30] None, however, focused on older adults, who due a higher prevalence of chronic diseases, may face additional risks from food insecurity. There has been increased attention on food insecurity in the general poverty and older populations, but neither face risks as high as the older homeless population.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research on homelessness and food insecurity has focused primarily on single adults and families in unstable (e.g. overcrowded or transient), substandard or unaffordable housing (3)(4)(5)(6)(7) . For example, a recent study of homeless mentally ill adults in Vancouver, Canada found that nearly two-thirds of the sample were food insecure (7) .…”
mentioning
confidence: 99%
“…Compared to the prevalence of food insecurity evaluated in 2010 in the general population living in the same urban area [22], the difference is striking (6.30% vs. 86.0%). Whereas this level of prevalence has already been observed in other studies focusing on homelessness [31][32][33][34], it is surprising and even worrying in France, a country that can be considered as a welfare state, ranking first among OCDE countries for the proportion of its GDP dedicated to public social expenditures.…”
Section: Discussionmentioning
confidence: 73%